2009
DOI: 10.1007/s10658-009-9450-2
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of Datura stramonium, Calotropis gigantea and Azadirachta indica against Fusarium mangiferae and floral malformation in mango

Abstract: Floral malformation caused by Fusarium mangiferae is a serious threat to mango cultivation in various countries. Different long-term measures suggested to control it were found to be unsuccessful. Present studies clearly showed strong antifungal activity of a concoction brewed from Datura stramonium, Calotropis gigantea, Azadirachta indica (neem) and cow manure (T 1 ) followed by methanol-water (70/ 30 v/v) extracts of Datura stramonium, Calotropis gigantea and Azadirachta indica (T 2 ) against Fusarium mangif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 50 publications
0
20
1
1
Order By: Relevance
“…Several of these weed species/Fusarium pairs had already been identified by Postic et al (2012) or Altinok (2013). Our observations are not consistent with an anticipated negative interaction due to the antifungal effects of the broadleaf weed Datura stramonium extract (Usha et al 2009). Our measurement remains purely statistical, so pairwise associates may reflect both causality or/and similar responses to any external environmental condition or agricultural practice.…”
Section: Interactions Between Variablescontrasting
confidence: 78%
“…Several of these weed species/Fusarium pairs had already been identified by Postic et al (2012) or Altinok (2013). Our observations are not consistent with an anticipated negative interaction due to the antifungal effects of the broadleaf weed Datura stramonium extract (Usha et al 2009). Our measurement remains purely statistical, so pairwise associates may reflect both causality or/and similar responses to any external environmental condition or agricultural practice.…”
Section: Interactions Between Variablescontrasting
confidence: 78%
“…The use of extract mixtures produced with D. stramonium and other plant species has shown antifungal potential against Fusarium mangiferae (USHA et al, 2009). Studies performed with pine bark substrate have shown that this may decrease fungicide applications for controlling damping-off in forest seedlings by inhibiting the pathogens that affect the root (CASTILLO, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Essential oils from Matricaria recutita and M. chamomilla have been used to inhibit the growth of saprophytic and opportunistic fungi like Aspergillus flavus, A. fumigatus, A. Niger, Trichoderma harzianum and Fusarium oxysporum (Tolouee et al, 2010;Jamalian et al, 2012). Similarly, extracts from the species Datura stramonium, Calotropis gigantea, and Azadirachta indica (neem) have been used to control Fusarium mangiferae (USHA et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The native wild Solanaceae D. stramonium from Tunisia (Chott-Mariem, Sousse) was used for the isolation of endophytic bacteria. Aqueous extracts [42], methanol extracts [43], petroleum ether, hexane, chloroform and ethanol extracts [15] from D. stramonium were extensively exploited for their antifungal activity against plant pathogenic fungi. However, few data were available on D. stramonium use as potent source of isolation of fungal [21,44] and bacterial biocontrol agents [11].…”
Section: Discussionmentioning
confidence: 99%